Analysis of Built-up Land Spatial Patterns Using Multitemporal Satellite Imagery in Pekalongan City - Nurhadi Bashit; Yudo Prasetyo; Abdi Sukmono (Politeknik Negeri Batam, 2020)
Regional growth is characterized by an increase in built-up land. An increase in built-up land can cause changes in land use such as vacant land turned into built-up land. One of the cities in Central Java that experienced an increase in built-up land was in the City of Pekalongan. Based on Pekalongan City Regulation Number 30 Year 2011, the National Spatial Planning stipulates that Pekalongan City is the Regional Activity Center. This causes the Pekalongan City to have the potential to increase the amount of built-up land. An increase in uncontrolled built-up land can cause negative impacts such as reduced water catchment areas so that the disruption of water resources conditions. Therefore, it is necessary to monitor the increase of built-up land in Pekalongan City and see its development spatial patterns. One of method for monitoring a city's built-up land uses the remote sensing method. This study uses an Index-based Built-up Index (IBI) algorithm. Based on the results of this study, it can be concluded that the city of Pekalongan experienced an increase in built-up land between 2013 and 2019. The largest increase in built-up land is in the range of 2017 to 2019 with an area of increase of 359.088 ha so that it can be obtained the speed of increase of built-up land by 170.544 ha/year. The spatial pattern of built-up land increased in 2017 to 2019 heading south because South Pekalongan Regency has a toll road that connects the main road with the toll road.